Predictors of Pharmacotherapy and Quality of Life Among Patients With Diabetic Foot Syndrome: A Cross-Sectional Study from a Tertiary Care Hospital in India. Issue 1 (March 2022) - Pasangha, E.; George, B.; Bhuvana, K. B.; Padmini, D.
Objective: To assess the patterns and predictors of pharmacotherapy and QOL in DFS patients in an Indian tertiary care hospital. Methods: A cross-sectional study was conducted among inpatients with DFS. Data on sociodemographic and clinical factors, pharmacotherapy, clinical outcomes, and QOL were analyzed using the chi-squared test, independent sample t -test, and binary logistic regression. Results: We screened 3284 inpatients and included consecutive 87 (2.7%) DFS patients. The mean age was 56.08 ± 11.05 years, with a male preponderance (75.8%). Mean HbA1c was 9.9 ± 2.483. About 75% of patients received insulin, and polypharmacy was noticed in 82.7%. About 67.8% of DFS patients had other vascular complications of diabetes, with diabetic retinopathy being the most common in 89%. Amputations were noticed in 32.1% of patients. Overall, poor QOL was seen in 79.3% of patients. The mean scores for different domains were as follows: physical, 41.51 ± 14.15; psychological, 42.90 ± 11.16; social relationships, 43.06 ± 19.36; and environment, 47.17 ± 13. The presence of complications from diabetes was a significant predictor of the utilization of antihypertensives (OR: 2.92, CI [1.09, 7.79], P = 0.03) and poor QOL (OR: 4.54, CI [0.965, 21.41], P = 0.05). Conclusion: DFS patients in this study were found to be younger with poor glycemic control and other vascular complications of diabetes. The presence of other complications of diabetes in DFS patients was found to be a predictor of pharmacotherapy and poor QOL.